3(x-4=2(x-6)

Simple and best practice solution for 3(x-4=2(x-6) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3(x-4=2(x-6) equation:



3(x-4=2(x-6)
We move all terms to the left:
3(x-4-(2(x-6))=0

See similar equations:

| 3x18=18+36 | | 1/4+3/4a=-(7/4a-1) | | 2-(x+7)=14x=2 | | 2x2-3x2+4=-12 | | (4x-34)=(2x) | | x2/4+3=7 | | -5-4x=-10-9x | | 5{x+3}=30 | | 4x2-5=-1 | | 36-f=16 | | (2x+12)=(2x-64) | | 3x2+4=28 | | x/x=5/40 | | (3x-6)+x=45 | | 4x2-5=11 | | 2x2+2=34 | | (3x)x30=90 | | 1/2v+11/12-5/4=-5/12 | | 4x2-6=10 | | 8-2(n+3)=n+7-n | | -9-6x=-6-5x | | 10q+3q+5=2(q-3)q= | | z/10=300 | | 50=5t+0.9375t^2 | | x-7=147 | | n/2=10/20 | | 6x-4=@ | | x2+21x+111=0 | | 1/3=3/n | | .3x-0.6x=1.25 | | 9x+48=x-32 | | 5+x2+14x-3=x(x-6)+82 |

Equations solver categories